Bioactive Compound Variability in a Brazilian Capsicum Pepper Collection. Issue 3 (16th June 2017) - Acunha, Tanize dos Santos; Crizel, Rosane Lopes; Tavares, Icaro Borges; Barbieri, Rosa Lia; Pereira de Pereira, Claudio Martin; Rombaldi, Cesar Valmor; Chaves, Fabio Clasen
Abstract : This report aims to characterize the bioactive content of pepper ( Capsicum L., Solanaceae) accessions from a Brazilian germplasm collection. Peppers are currently a major vegetable crop worldwide, with 31 Tg produced in 2013, according to FAO. Seventy‐two accessions of Capsicum annuum L., C. baccatum L., C. chinense Jacq., and C. frutescens L. were evaluated and high variability was observed in soluble solids, pH, acidity, fruit color, total phenolic content, total carotenoid content, antioxidant potential, and capsaicinoid content. Accessions P119, P302, and P189 had the highest phenolic compound contents, which ranged from 225.16 to 243.47 mg gallic acid equivalent 100 g −1 . The highest antioxidant potential observed ranged from 2.71 to 3.03 mmol Trolox equivalent 100 mg −1 in accessions P287, P50, and P25. Maximum carotenoid content was seen in accessions P269, P280, and P179, which contained between 53.42 and 54.11 mg β‐carotene equivalent 100 g −1 . Capsaicinoid content was highest in accessions P120, P246, and P236 and ranged from 6132.00 to 19, 543.70 mg 100 g −1 . Capsaicin and dihydrocapsaicin represented, on average, 79% of the total capasaicinoid content. No one accession contained high levels of multiple bioactive compounds.